COMPLIANCE ANALYSIS OF TRADERS PAYING ZAKAT WITH ANALYTICAL NETWORKING PROCESS APPROACH IN CENTRAL ACEH DISTRICT - Falahuddin, Falahuddin; Fuadi, Fuadi; Munardi, Munardi; Khairisma, Khairisma; Nurmalita Sari, Dina (CV. Radja Publika, 2022)
This research is crucial because it is vital to conduct an in-depth study by integrating theoretical and field research addressing the perspectives of business actors in Takengon City on fulfilling their zakat commitments as Muslims. Moreover, whether or not they are obedient, they must pay the commercial zakat. Due to the fact that the majority of Takengon's population adheres to the Islamic faith, the potential is fairly substantial. This study aims to determine whether or not traders who have reached their zakat payment limit are obedient. Research evaluation This is a descriptive study of zakat management organizations, academic institutions, government agencies, and practitioners. The technique employed is a technique of purposive sampling, and the subject of this study is the zakat experts in Baitul Mal Takengon. This study will explain the ways that induce traders to pay zakat dutifully. The results of the study are anticipated to impact future policies that will raise the level of life, support the occurrence of healthy economic growth, and provide a remedy for traders' lack of awareness regarding the payment of their commercial zakat.